Central bank liquidity facilities and market making - David A. Cimon; Adrian Walton (Bank of Canada, 2022)
In the onset of the COVID-19 crisis, central banks purchased large volumes of assets in an effort to keep markets operational. We model one such central bank, which purchases assets from dealers to alleviate balance sheet constraints. Asset purchases can prevent market breakdown, improve price efficiency and reduce dealer risk positions. A central bank that purchases assets at their expected value is able to achieve market outcomes as if dealers were unconstrained. Absent other concerns, central banks can maximize welfare by purchasing assets at a premium, though they may create market distortions. Alternatively, central banks who bear costs associated with large interventions may only be willing to purchase assets at a discount. In the absence of leverage constraints, lending programs are as effective as asset purchases; when leverage constraints are present, lending programs lose effectiveness.
Keywords: G10; G20; L10; 330; Coronavirus disease (COVID-19); Economic models; Financial institutions; Financialmarkets; Market structure and pricing